SHEAR BEHAVIOUR ANALYSIS OF REINFORCED CONCRETE BEAM USING NON-LINEAR FINITE ELEMENT SIMULATION - Rahmat Dwi Sutrisno; Harun Alrasyid; Wahyuniarsih Sutrisno (Institut Teknologi Sepuluh Nopember, 2022)
This paper investigates shear behaviour of reinforced concrete using multi-surface plasticity model. This analysis uses nonlinear finite element simulation using 3D-NLFEA finite element package. The experimental data adopted from the results of experimental test on eighteen beams where nine beams carried out by Bresler and Scordelis in 1963 and similar nine beams carried out by Vecchio and Shim in 2004. The constitutive model for the concrete material which used in this simulation is based on the plasticity-fracture model and considered the tension stiffening effect for the concrete. The result of the numerical simulation latter compared with the experimental test including load-deflection response, cracking pattern, and failure mode. Based on the analysis result, it was found that the load-deflection response shows slightly higher response compared with the experimental result. However, the cracking pattern and failure mode of the beam shows good result which is in compliance with the experimental test.